Microscopic anatomy of gonadal area in the deep-sea clam Calyptogena pacifica (Bivalvia: Vesicomyidae) with emphasis on somatic cells. (April 2022) - Yurchenko, Olga V.; Borzykh, Oleg G.; Kalachev, Alexander V.
Highlights: Interacinar space is filled by hemocytes and muscle cells. In males, numerous accessory cells are present in pre-spawning acini. In females, accessory cells do not form follicle around oocytes. Abstract: Somatic cells in the gonadal area of male and female deep-sea clams, Calyptogena pacifica, were examined using light and transmission electron microscopy. Acini both at the pre-spawning stage and at the stage of active spermatogenesis were observed to be simultaneously present in sections through a male gonad. Oocytes of various degrees of maturity were simultaneously present in female acini. No storage tissue and cells similar to adipogranular cells or vesicular connective tissue of other mollusks were found in the gonadal area of C . pacifica . Instead, in both males and females, numerous hemocytes surround the acini. Among hemocytes, two types of granulocytes and erythrocytes were identified. Bundles of muscle cells were also found in the interacinar space. Male intraacinar accessory cells were rather large, glycogen-rich, with lipid inclusions, and phagosomes contained spermatogenic cells. Female accessory cells had well-developed endoplasmic reticulum, but they did not form any follicles around oocytes, being in their basal part, closer to basal lamina. Such a specific pattern of gonad organization can presumably be explained by both symbiosis with sulfide-oxidizing bacteria and phylogenetic aspects that should be further studied. Some evidence for continuous gametogenesis are discussed.